PENGOLAHAN AIR LIMBAH LABORATORIUM DENGAN MENGGUNAKAN SISTEM KOMBINASI ADSORPSI DAN FITOREMEDIASI - , EKO SISWOYO, Prof. Dr. Sudarmadji, M.Eng.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Activities of laboratory produce wastewater with quite high hazardous materials, therefore it is needed a good wastewater treatment plant before dispose the wastewater to water bodies to protect environment. Recently, most laboratory of university in Indonesia do not treat their wastewater in term of technology and cost problem. This condition will give bad impact to the environment. This research is conducted to investigate the removal efficiency of mercury (Hg) from laboratory wastewater by utilizing adsorption with activated carbon combined to phytoremediation with water hyacinth and water spinach. This research used both artificial wastewater and laboratory wastewater of Environmental Engineering Department, Islamic University of Indonesia Yogyakarta. Wastewater is flowed to the reactor with activated carbon for 0, 2, 4, 6 and 8 hours and then continued with phytoremediation reactor for 0, 3, 6, 9 and 12 days as contact time. It was shown that the efficiency of activated carbon in removing Hg from laboratory wastewater was 97,33% after 6 hours of contact time and the efficiency of water hyacinth was 96% after 6 days of contact time. The combination of adsorption with activated carbon and phytoremediation with water hyacinth or water spinach can remove Hg in wastewater almost 100%. It was clear that this system can be applied to remove Hg from laboratory wastewater.